Coronary Subclavian Steal Syndrome Causing Acute Myocardial Infarction in a Patient Undergoing Coronary-Artery Bypass Grafting - Jiri Mandak; Miroslav Lojik; Martin Tuna; James Lago Chek (Case Reports in Medicine)
Coronary subclavian steal syndrome with retrograde blood flow in the left internal mammary-coronary bypass graft is a rare but severe complication of cardiac surgery. The authors present a case of a 68-year-old man after coronary-artery bypass grafting using an internal mammary artery. He had been suffering from angina pectoris for the last several years before surgery. The patient was resuscitated at home by emergency medical service because of primary ventricular fibrillation due to an acute myocardial infarction 5 years after surgery. An occlusion of the left subclavian artery with the retrograde blood flow in the left internal mammary coronary bypass was found. This could have been the cause of insufficiency in coronary blood flow and ischemia of the myocardial muscle. The subclavian artery occlusion was successfully treated with percutaneous transluminal angioplasty and implantation of 2 stents. The patient remained free of any symptoms 2 years after this procedure.